Watkins and Graham Families at Fresno's Historic Water Tower - Watkins, Howard::::::::: (1989)
Vertical view of Fresno's Historic Water Tower; Pictured: Adam Watkins, Richard Graham, Robin Watkins, Veronica Velasquez, Peter Graham and Jesse Graham